Analysis of Elasto-plastic Contact and Accuracy Loss of Planetary Roller Screw Pair Considering Radial Load - Yuhao Zhang; Guangwu Zhou; Guicheng Wu (Jixie chuandong)
The elasto-plastic deformation of planetary roller screw pair under short-term high overload will reduce the transmission accuracy and increase the friction torque，which will affect the service life. Moreover，the radial load and pitch error have immense influence on the contact load of all threads. Therefore，the calculation model of elasto-plastic contact and accuracy loss of planetary roller screw pair is established. The residual plastic deformation is calculated by the finite element method. The effects of radial load，pitch error，thread number，contact angle and helix angle on the residual plastic deformation are analyzed. The residual plastic deformation decreases with the increase of thread number and thread rising angle，and increases with the increase of contact angle. When the contact angle is 36°~40° and helix angle is 1°~5°，the accuracy loss is small. The increment of axial load aggravates the accuracy loss of planetary roller screw pair. Although the radial load is beneficial to reduce the accuracy loss，it will aggravate the uneven distribution of plastic deformation between rollers.